Applications of α, ω‐telechelic polydimethylsiloxane as cross‐linkers for preparing high‐temperature vulcanized silicone rubber. (7th January 2019) - Dong, Fuying; Wang, Xianpeng; Li, Shuaijie; Hao, Jiawen; Tang, Xinde; Kuang, Rui; Wang, Yanmin; Feng, Shengyu
Abstract : Multiamino‐terminated telechelic polydimethylsiloxane (MATTPS) was synthesized via aza‐Micheal reaction and amidation reaction and subsequently employed as cross‐linkers of polysiloxane containing γ ‐chloropropyl groups (CPPS) for preparing a series of high‐temperature vulcanized silicone rubber (MCSR/MATTPS). The curing, mechanical, and thermal properties of MCSR/MATTPS were studied through rheometry, mechanical testing, and thermogravimetric analysis (TGA). MCSR/MATTPS exhibits optimal mechanical properties with a tensile strength of 9.52 MPa and tear strength of 45.4 kN/m when the molar ratio of [N–H]/[CH2 CH2 CH2 Cl] is of 1, which is attributed to the formation of concentrative cross‐linking in the three‐dimensional polymer networks. The thermal behaviors of MCSR/MATTPS display a two‐step weight loss process by heating in nitrogen whereas more than two weight loss process in air. TGA results indicate that the introduction of aliphatic long chain and carbonyl groups in the structure of MATTPS has little negative effect on the thermal stability of MCSR/MATTPS.